The Influence Of Work Enthusiasm And Work Discipline On The Work Productivity Of Employees Of The Fisheries Service Of The Four Lawang District - Wati, Putri Setia; Hardiyansyah; Aprini , Nisma (Universitas Dehasen Bengkulu, 2024)
abstrak